KNOWLEDGE NETWORKS: EFFECTS ON TOURISM DESTINATION COMPETITIVENESS - Nikolovski, Branko (Horizons - International Scientific Journal, 2022)
Tourism market shelves contain composite products and thus requirement for alliances and collaboration between various local actors is very high. We can easily illuminate an argument that in the global tourism market, destinations are those players that compete for more costumers, not individual business operators. In this sense, innovation becomes crucial for building competitiveness, and leads as to understanding of how destinations source, share and use knowledge. Once we utilize the destination as a network of stakeholders (i.e. network system nodes- enterprises, government bodies, destination management organizations, etc.), it becomes clear that destination functions by the movement of information and investment through the network. In itself, this is an innovative notion of a destination because underlines managing knowledge across complex network systems as a crucial to this process. In this paper we are examining the benefits of knowledge network configuration linked to the competitive performance of destinations.